The Development of Electromedical Technology in Enhancing Healthcare Quality in Indonesia - Permana Yoga Utama, Yuris (Lafadz Jaya Publisher, 2024)
The advancement of electromedical technology has had a significant impact on improving healthcare quality in Indonesia. This technology encompasses a range of devices, such as MRI scanners, ECG monitors, and remote patient monitoring systems, which play essential roles in enhancing diagnostic accuracy, expediting medical decision-making, and enabling real-time patient monitoring. However, the adoption of electromedical technology in Indonesia faces several challenges, including budget limitations, a shortage of trained healthcare professionals, and complex regulatory frameworks. This article examines the current state of electromedical technology implementation in Indonesian healthcare settings, highlighting both its benefits and the barriers to its widespread use. By reviewing case studies from Indonesian hospitals, the article explores the positive effects of electromedical devices on healthcare quality and outcomes, as well as the logistical and financial obstacles encountered in their integration. The study also offers recommendations for addressing these challenges, including increased investment in healthcare infrastructure, targeted training programs for medical professionals, and streamlined regulatory processes to facilitate the use of advanced medical technologies. Through a comprehensive literature review and case analysis, this research aims to provide a deeper understanding of how electromedical advancements contribute to healthcare improvements in Indonesia and to suggest strategies for maximizing their impact across diverse healthcare settings.